Energy-efficient chamber dryer with combined heating heat transfer - Petrova, Zh.; Vyshnevskyi, V. (Energy and Automation, 2024)
Chamber dryers are widely used in the processing of vegetables and fruits in Ukraine, the USA, China, France, etc. They are intended for drying lumpy (artificial) products (bread, chopped vegetables and fruits, etc.). A chamber dryer is a connection of one or more dryer cabinets in location mode. In a 2-zone chamber dryer, it is possible to dry large volumes of raw materials, which consumes less energy compared to the power that the entire drying cabinet has when it is operated separately. But high energy costs for the process of drying materials with high prices for the second encourage to solve the task of increasing energy efficiency when creating new chamber dryers using electronic heaters of the coolant.The Institute of Technical Thermal Physics of the National Academy of Sciences of Ukraine suggests using steam heat generators in the operation of a multi-zone tunnel dryer, which, in comparison with organic fuel heat generators, make it possible to save heat consumption by 1.7-2.3 times compared to existing analogues. Energy consumption of heat in the tunnel dryer is 3800 kJ/kg of evaporated moisture.To reduce energy costs, solar tunnel dryers with an increase in the heat exchange surface due to the maximum separation of pallets with raw materials at different angles have become widespread. Due to the influence of solar energy, the temperature of the drying agent can reach 70 °С.The main direction of the development of drying plant materials is the combination of existing technologies with renewable energy sources, in particular the use of solar energy, heat pumps, as well as microwave, infrared and sublimation drying.Combined drying technology is the combination of two or more different drying processes that can provide a synergistic effect, resulting in reduced energy requirements and reduced drying time while maintaining most of the quality characteristics, such as taste, nutrients, color, aroma, texture, etc.Different methods of combined drying are considered, such as: solar-infrared, convective-infrared, infrared-microwave, convective-microwave and multifunctional, which combines microwave-sublimation drying under vacuum. The comparison of the combined methods showed a significant decrease in the duration of drying and a reduction in energy consumption, which can be used in the design of tunnel energy-efficient dryers.Key words: energy-efficient methods of drying, heat and mass transfer, thermophysical properties, thick-film heating elements, infrared radiation, combined drying